2014
DOI: 10.1586/14737140.2014.866043
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocele: prevalence and management in gynecological malignancies

Abstract: A lymphocele is a cystic mass that may occur in the retroperitoneum following a systematic pelvic and/or para-aortic lymphadenectomy. Lymphoceles may be the cause of severe morbidity, or rarely mortality. Symptomatic lymphoceles manifest with pain, compression of adjacent structures, lymphoedema, deep vein thrombosis or inflammation. The morbidity associated with a symptomatic lymphocele may reduce the quality of life of a patient, as well as delay subsequent cancer treatment. The number and positivity of remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 71 publications
1
55
1
2
Order By: Relevance
“…Pelvic lymphocele is typically found incidentally during routine CT follow-up after surgery; however, it is sometimes symptomatic, requiring treatment [9][10][11]21]. In gynaecology and urology, several studies have shown that pelvic lymphocele is one of the most common complications after pelvic lymphadenectomy [12,13,22,23]. There have been many studies reporting complications associated with LPND following rectal cancer surgery [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelvic lymphocele is typically found incidentally during routine CT follow-up after surgery; however, it is sometimes symptomatic, requiring treatment [9][10][11]21]. In gynaecology and urology, several studies have shown that pelvic lymphocele is one of the most common complications after pelvic lymphadenectomy [12,13,22,23]. There have been many studies reporting complications associated with LPND following rectal cancer surgery [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Lateral pelvic lymph node (LPN) metastasis has been reported to occur in 17. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].4% of patients with locally advanced lower rectal cancer [1,2]. The treatment strategy for lower rectal cancer differs between Western countries and Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may rarely affect the ureter and bladder (hydronephrosis, urinary frequency), bowel (ileus, tenesmus), or vessels (thrombosis) and cause abdominal pain. Lymphoceles may also become infected (1,2) . The incidence of lymphoceles after gynecologic cancer surgery is reported as 1-58%.…”
Section: Introductionmentioning
confidence: 99%
“…Тем не менее пациенты, перенесшие лимфодиссекцию, часто страдают от различных послеоперационных осложнений, в частности обусловленных нарушением целостности лимфатического аппарата. Стенка лимфатического сосуда содержит малую долю гладкой мускулатуры и не способна к вазоконстрикции, вследствие этого лимфатические сосуды остаются в открытом состоянии в течение 48 ч после травмы [3]. Массивное повреждение лимфатических сосудов в результате лимфодиссекции приводит к развитию послеоперационных лимфатических осложнений -лимфатических кист, лимфедемы, лимфореи [4].…”
Section: Introductionunclassified